Correction: Epitaxial growth of β-Ga2O3 (−201) thin film on four-fold symmetry CeO2 (001) substrate for heterogeneous integrations. Issue 48 (2nd December 2021) - Tang, Xiao; Li, Kuang-Hui; Liao, Che-Hao; Zheng, Dongxing; Liu, Chen; Lin, Rongyu; Xiao, Na; Krishna, Shibin; Tauboada, Jose; Li, Xiaohang
Abstract : Correction for 'Epitaxial growth of β-Ga2 O3 (−201) thin film on four-fold symmetry CeO2 (001) substrate for heterogeneous integrations' by Xiao Tang et al., J. Mater. Chem. C, 2021, 9, 15868–15876, DOI: ; 10.1039/D1TC02852A .